Why neuroscience cannot detect our ordinary practical problems: On the basic fallacy of radical neuroscientists - Haba, Enrique P. (2026)
Some neuroscientists ―those I would call the “radical” ones― postulate an absolute neurological determinism of human consciousness. According to them, human thinking and behaviour are composed solely of epiphenomena, which are determined by certain neurological processes. However, these scientists miss differentiating necessary conditions from sufficient conditions;  they fully believe in the logic of this fallacious theoretical thinking. Based upon such axiomatic pre-understanding, these kinds of studies infer false generalizations about the matter of their research.